Innovation in family business - De Massis, Alfredo (Henry Stewart Talks, 2015)
Introduction to innovation in family business, Family governance and innovation, Product innovation management in family vs. non-family SMEs, External technology acquisition in family vs. non-family firms, Temporal evolution of proactiveness in family firms, Organizational goal diversity and transgenerational innovation, The ability and willingness paradox in family firm innovation, Innovation through tradition